Study of the efficiency of a hybrid pumping system (photovoltaic/ electric) for better rural setting management - Mebrek N.; Bouziane M.T.; Demnati F.; Nemdil A.E. (Research and innovation as tools for sustainable agriculture, food and nutrition security, 2020)
The Maghreb countries, particularly Algeria have a high solar potential. The German Space Agency (DLR), showed exceptional sunshine levels, of 1200 kWh/ m2/ year in Northern Great Sahara. According to satellite evaluation, the German Space Agency (ASA) concluded that Algeria represents the most important solar potential of Mediterranean basin, i.e.: 169.000 TWh/year for thermal solar, 13.9 TWh/year for solar photovoltaic. Currently, this renewable energy represents a response to the environmental problems and also a sustainable solution to the current energy crisis. In Algeria, electricity consumption in agricultural sector represents a significant part of national consumption. Farms in the Saharan regions use the diesel group to satisfy the electrical energy needs in case of electricity lack (due to failures or farms isolation). In this context, a study was carried out at the laboratory of renewable energy of the University of Biskra, in which the main aim is to determine the hybrid pumping system efficiency, a system powered with the electrical energy and another with photovoltaic energy. The data obtained showed that the two systems have similar efficiency. This confirms that photovoltaic resource use for irrigation is the best economic compromise for sustainable agricultural development in isolated arid regions.
2. MEDFORUM 2018, 2018/09/18-20, Bari (Italy)